Age-related Carbonylation of Fibro-cartilage Structural Proteins Drives Tissue Degenerative Modification - Scharf, Brian (2013)
Aging-related oxidative stress has been linked to degenerative modifications in different organs and tissues. Using redox proteomic analysis and illustrative MS/MS mapping we demonstrate oxidative post-translational modifications in structural proteins of intervertebral discs (IVD) isolated from aging mice. Increased protein carbonylation was associated to protein fragmentation and aggregation. Complementing these findings, a significant loss of elasticity and increased stiffness was measured in fibrocartilage from aging mice. Studies employing circular dichroism and intrinsic tryptophan fluorescence revealed a significant loss of secondary and tertiary structures of purified collagens following oxidation. Collagen unfolding and oxidation promoted both non-enzymatic and enzymatic degradation. Importantly, induction of oxidative modification in healthy fibrocartilage recapitulated the biochemical and biophysical modifications observed in the aging IVD. Together, these results suggest that protein carbonylation, glycation, and lipoxidation could be an early event in promoting IVD degenerative changes.